Government Public Communication Strategy Through Social Media In the Digital Era (Case Study on Bangli Regency Government) - Desak Tri Mahadewi; Gede Sri Darma (Eduvest - Journal of Universal Studies, 2024)
Communication strategies play a very important role in helping programs in government institutions to be more effective. Because communication strategies will be able to help effectively develop relationships, improve reputation and persuade people to act. The aim of this research is to respond to the background explanation above, the problem formulation that needs to be addressed in this research is: (1) to determine the application of public communication current government (2) to analyze the Bangli Regency government's public communication strategy through social media (3) to determine the supporting and inhibiting factors for communication strategies carried out through social media. This research is descriptive in nature with a qualitative approach. Data sources include primary data obtained through the interview process and secondary data originating from documents related to the research. The sampling method is purposive sampling where this technique includes people who are selected based on certain criteria. Respondents in this research were the Regent of Bangli Regency, Head of the Communication and Information Service, Head of Information, Public Relations Officer, Social Media Admin and the community. Then, data collection techniques used interviews, observation and documentation. Data analysis techniques using data reduction, data collection and data presentation.